Bugs - "York, Penelope" (DK London, 2015)
Eyewonder Bugs explores all types of bugs from an insect that looks like a twig to a butterfly that tastes with its feet! From sand devils burrowing in the desert to busy bees, these creepy crawlies come in all shapes and sizes and can do amazing things